The Effect of Working Capital and Operational Costs on Net Income in Automotive Companies and Components Listed on the Indonesia Stock Exchange (IDX) - Salma, Nur; Sari, Meita Sekar; Silvia, Dewi; Ismawati, Ismawati (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study was to determine the effect of working capital variables and operational costs on net income. The independent variable used in this study is working capital and operational costs while the dependent variable used in this study is net income. The population in this study are automotive sector and component companies listed on the IDX. The number of samples is 30 financial report data. The method of determining the sample used is purpose sampling. The analytical tool used in this study is the multicollinearity test, and heteroscedasticity test. The statistical analysis used is multiple linear regression analysis, and hypothesis testing consisting of t test and f test and determination coefficient (R2). The results showed that the partial test results (t test) of the study stated the significance of working capital (0,006), and operational costs (0,000). And simultaneous results (f test) of the study state significance (0.001), which means simultaneously working capital and operational costs for net income. For R2 test 0.407, it means that 40.7% of net profit is influenced by working capital, and operational costs. While the rest is influenced by other variables outside of the variables used in this study